Genomic study of TEX15 variants: prevalence and allelic heterogeneity in men with spermatogenic failure - Qureshi, Sidra; Hardy, Jimmaline J.; Pombar, Christopher; Berman, Andrea J.; Malcher, Agnieszka; Gingrich, Tara; Hvasta, Rachel; Kuong, Jannah; Munyoki, Sarah; Hwang, Kathleen; Orwig, Kyle E.; Ahmed, Jawad; et al. (Frontiers in Genetics, 2023)
Human spermatogenesis is a highly intricate process that requires the input of thousands of testis-specific genes. Defects in any of them at any stage of the process can have detrimental effects on sperm production and/or viability. In particular, the function of many meiotic proteins encoded by germ cell specific genes is critical for maturation of haploid spermatids and viable spermatozoa, necessary for fertilization, and is also extremely sensitive to even the slightest change in coding DNA. Here, using whole exome and genome approaches, we identified and reported novel, clinically significant variants in testis-expressed gene 15 (TEX15), in unrelated men with spermatogenic failure (SPGF). TEX15 mediates double strand break repair during meiosis. Recessive loss-of-function (LOF) TEX15 mutations are associated with SPGF in humans and knockout male mice are infertile. We expand earlier reports documenting heterogeneous allelic pathogenic TEX15 variants that cause a range of SPGF phenotypes from oligozoospermia (low sperm) to nonobstructive azoospermia (no sperm) with meiotic arrest and report the prevalence of 0.6% of TEX15 variants in our patient cohort. We hypothesize that SPGF phenotype severity is dictated by individual TEX15 variant’s impact on structure and function. Resultant LOFs likely have deleterious effects on cross over/recombination in meiosis. Among identified possible LOF variants, one homozygous missense substitution c.6835G>A (p.Ala2279Thr) co-segregated with cryptozoospermia in a family with SPGF. Additionally, we observed numerous cases of inferred in trans compound heterozygous variants in TEX15 among unrelated individuals with varying degrees of SPGF. Variants included splice site, insertions/deletions (indels), and missense substitutions, many of which resulted in LOF effects (i.e., frameshift, premature stop, alternative splicing, or potentially altered posttranslational modification sites). In conclusion, we performed an extensive genomic study of familial and sporadic SPGF and identified potentially damaging TEX15 variants in 7 of 1097 individuals of our combined cohorts, supporting the notion of increased gene variant frequency in SPGF and its genetic and allelic heterogeneity as it relates to complex disease such as male infertility.